2020
DOI: 10.1590/fst.15519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment for liquefaction and pasteurization on antioxidant activity and phenolic compounds of Astragalus and sunflower-cornflower honeys

Abstract: On this study, effect of heat treatments (liquefaction at 55 °C for 12 h and pasteurisation at 90 °C 15 sec) on total phenolic content, antioxidant activity and phenolic compounds of astragalus and sunflower-cornflower honeys was investigated. Total phenol content and antioxidant activity of honeys were assessed by Folin-Ciocalteu and ABTS methods, respectively. Phenolic profile was determined by HPLC-DAD system. Dnly pasteurisation process had a significant impact on sunflower-cornflower honey with regard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Heat treatment causes an increase in antioxidant components [36]. In this study, the antioxidant and anti-inflammatory activities of the HL extracts increased with heat treatment.…”
Section: Heat Treatment Increased the Contents Of Bioactive Compoundssupporting
confidence: 51%
“…Heat treatment causes an increase in antioxidant components [36]. In this study, the antioxidant and anti-inflammatory activities of the HL extracts increased with heat treatment.…”
Section: Heat Treatment Increased the Contents Of Bioactive Compoundssupporting
confidence: 51%
“…According to Šarić et al [19], heating honey at 95°C for 5 min no longer affects its antioxidant activity and total phenolic content. Aydogan-Coskun et al [20] commented that the simple phenolics could increase due to the breakdown of supramolecular structures containing phenolic groups.…”
Section: Total Phenolic and Flavonoidmentioning
confidence: 99%
“…Boletus aereus and Pleurotus cornucopiae are two kinds of rare edible and medicinal fungus with high medicinal value . In recent years, studies have shown that polysaccharide from Boletus aereus and Pleurotus cornucopiae have some interesting biological activities, such as bacteriostasis, antioxidation, et al (Hagiwara et al, 2005;Wang et al, 2013;Wu et al, 2014;Minato et al, 2017;Lee et al, 2017;Zhang et al, 2014). However, there are some differences in the structure of polysaccharides from different regions, and there is no report on the study of the polysaccharides of Boletus aereus and Pleurotus cornucopiae from Litang county of Sichuan Province.…”
Section: Introductionmentioning
confidence: 99%